The Implementation of School Literacy Movement in SMP Laboratorium Undiksha Singaraja - Widiasih, Putu Sri; Tantra, Dewa Komang; Pratiwi, Ni Putu Astiti (Universitas Pendidikan Ganesha, 2022)
This research aimed at how was the school literacy program implemented in SMP Laboratorium Undiksha Singaraja. Mixed-method was used because the data of this research were analyzed quantitatively and qualitatively. There were six findings showed that the financial resources were getting from BOS fund and book donation. The time resources that students read books around 15 minutes before whilst-activity in the classroom while this school has special schedule in outside classroom that was called happy Friday. The facility resources were library, laboratory rooms, reading corner, and multimedia area in good condition. The processes of implementation were conducted in three stages; introduction stage, implementation stage, and establishment stage. The output measurements were through teachers’ evaluation, checking students’ project, checking students’ performance, students and teachers achievement, checking library visit, and students’ achievement in national exam. Furthermore, the sixth finding showed the impacts of reading motivation and reading habit were in moderate category.